Trade patterns and the ecological footprint a theory-based empirical approach - Thi Anh Dam; Markus Pasche; Niclas Werlich (Friedrich Schiller University Jena, 2017)
With global specialization and trade, countries make directly but also indirectly use of the environment via traded goods. Based on the theory of comparative advantages, the Heckscher-Ohlin-Vanek approach, we are using the Ecological Footprint as a broad measure of environmental use because its methodology explicitly accounts for the environmental use embodied in the traded goods. The comparative advantages depend on the endowment of environment as well as on the stringency of environmental policy which regulate the access to these factors. We empirically analyse the determinants of the ecological side of the trade pattern, i.e. whether the net export of the Ecological Footprint, embodied in the traded goods, depends on the comparative advantages as predicted by the theory, but also on a couple of control variables. A special focus is put on the role of environmental policy stringency which links our analysis to the "Pollution Haven" hypothesis. We also briefly analyse the role of FDI flows for the emergence of the ecological specialization pattern of production and trade.
Keywords: F18; F14; F11; Q57; Q56; 330; comparative advantage; Ecological Footprint; environmental policy; FDI; Pollution Haven; Trade